-3x-y=-12

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Add 3x to both sides of the equation.

-y=-12+3x

Multiply each term in -y=-12+3x by -1

Multiply each term in -y=-12+3x by -1.

(-y)⋅-1=(-12)⋅-1+3x⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=(-12)⋅-1+3x⋅-1

Multiply y by 1.

y=(-12)⋅-1+3x⋅-1

y=(-12)⋅-1+3x⋅-1

Simplify (-12)⋅-1+3x⋅-1.

Simplify each term.

Multiply -12 by -1.

y=12+3x⋅-1

Multiply -1 by 3.

y=12-3x

y=12-3x

Reorder 12 and -3x.

y=-3x+12

y=-3x+12

y=-3x+12

y=-3x+12

Using the slope-intercept form, the slope is -3.

m=-3

Find the Slope -3x-y=-12